David Joris and Dutch Anabaptism, 1524-1543 - Waite, Gary K., 1955- (Wilfrid Laurier University Press, 1990)
Waite's biography of Joris concentrates on his career as a DutchAnabaptist instead of his later, better-known activity as a Spiritualistin Basel. Waite argues convincingly that, from 1536 to 1539, Joris wasthe most influential Anabaptist leader in the Netherlands. Adopting amiddle path between the revolutionary chiliasm of the M?nsterAnabaptist kingdom and the radical separatism of Menno Simons and hisflock, Joris sought to unite the splintered Melchiorite movement underhis leadership. However, as Waite notes, history has been unkind to Joris: largelyignored by historians (the last book-length.